APLIKASI BUNGKIL INTI SAWIT MELALUI PEMBERIAN ENZIM RUMEN DAN FERMENTASI SEBAGAI BAHAN PAKAN IKAN NILA BEST (Oreochromis niloticus) - Nadisa Theresia Putri; Limin Santoso; Reza Samsudin (Jurusan Perikanan dan Kelautan, 2013)
An important factor on tilapiaaquaculture (Oreochromis niloticus) isthe availability of food in sufficient quantity,unfortunetely soybean meal and fishoil as feed ingredients are imported. Alternativefeedstuffs needed to solve the problemof limited soybean meal. Indonesia isthe largest producer of palm oil by-productcalled palm kernel meal (PKM). The studywas conducted to determine the effect ofthe addition of rumen enzyme and fermentationon nutrient digestibility determinesthe level of PKM and PKM as a feed ingredientfor tilapia growth. This research usedcompletely randomized design with 7 treatmentsand 3 replications. BEST tilapia withtotal weight of 23.83 ± 1.39 g / fish wereused. Data were analyzed using analysis ofvariance and followed by Duncan test. Thestudy shows that the use of BIS fermentedwith rumen enzymes and Trichoderma reeseiprovide the best nutrition and digestibilitycompared to other treatments. Nutrientcontent and digestibility of total protein(83.73%), carbohydrate (65.46%), energy(77.77%) and total digestibility (58%).